Komunikasi Public Relations dalam Program Corporate Social Responsibility Talent Udjo - Dwi Putri Budiawan; Maman Suherman (UNISBA Press, 2023)
Abstract. Government policies oblige companies to carry out CSR programs in the environment around the company aiming to bring companies closer to the community. PT. Saung Angklung Udjo dedicates its CSR program